Dying to Be Beautiful : The Fight for Safe Cosmetics - Kay, Gwen (Book collections on Project MUSE., 2005)
Tells the story of how cosmetics came to be regulated in early 20th century America. Examines the cosmetics industry in light of the 1938 Food, Drug, and Cosmetics Act.